Long-term results of transcervical, intrauterine ultrasound-guided radiofrequency ablation of uterine fibroids with the Sonata System: a retrospective follow-up studyAJOG Global Reports at a Glance - Julia F. van der Meulen, MD; Tessel H. Cooijmans, MD; Virrie J. van Zutven, MD; Jaklien C. Leemans, PhD; Corine J. Verhoeven, PhD; Marlies Y. Bongers, MD, PhD (Elsevier, 2022)
BACKGROUND: The Sonata System is a new minimally invasive, transcervical, uterine-sparing treatment option for fibroids with a mainly intramural location. The device combines intrauterine ultrasonography with radiofrequency ablation. Long-term follow-up data are still lacking. OBJECTIVE: This study aimed to evaluate long-term outcomes of the Sonata System in terms of surgical reintervention and to identify factors predicting surgical reintervention. Moreover, patient satisfaction, fibroid size reduction, and complication rate were evaluated. STUDY DESIGN: We performed a retrospective single-center cohort study of 53 women who underwent Sonata treatment between December 2011 and April 2019. Medical chart review was conducted to collect data on surgical reintervention and patient, fibroid, and surgery characteristics. The follow-up period lasted from date of initial surgery until April 2020. In addition, women filled out a questionnaire at a single time point (April 2020) containing questions about surgical reintervention and patient satisfaction.Kaplan-Meier analysis was used to determine cumulative reintervention rates and median time without reintervention. Univariate Cox regression analyses were performed to identify factors predicting surgical reintervention. RESULTS: Median follow-up period was 36 months (interquartile range, 22-58). Twenty-four women (45.3%) underwent a surgical reintervention, of which most were hysteroscopic myomectomies (45.8%). Surgical reintervention rates as determined by Kaplan-Meier analysis at 1-year and 2-year follow-up were 24.5% and 39.8%, respectively.Eventually, 7 women (13.2%) underwent a hysterectomy after the Sonata treatment. Univariate Cox regression analyses were performed, but did not show a significant association between surgical reintervention and age, preoperative fibroid size, type of ablated fibroid, number of ablated fibroids, and presence of other fibroids that could not be ablated during the Sonata procedure. Median fibroid diameter was 41 mm (interquartile range, 29-50) before and 29 mm (interquartile range, 20-40) after treatment (Z=−5.01; P<.001; 95% confidence interval, −13.0 to 7.0). Thirty-four women (69.4%) were satisfied with the treatment effect, and 42 women (85.7%) would recommend the Sonata treatment to other women. No device-related complications occurred. CONCLUSION: The Sonata System is a safe and minimally invasive treatment option for women suffering from (partly) intramural fibroids. The findings of this long-term follow-up study support counseling women for treatment with the Sonata System. More prospective studies with long-term follow-up are needed to investigate for which type and size of uterine fibroid the Sonata System is of most value.